Kajian Identitas Visual Video Travel Pariwisata Indonesia "Wonderfull Indonesia: A Visual Journey" Yang Memicu Reaksi Youtuber Mancanegara - Dwisanto Sayogo (AKSA: Jurnal Desain Komunikasi Visual, 2017)
In December 2016, a travel video uploaded on Youtube entitled "Wonderfull Indonesia; A Visual Journey. " the purpose of the video is to increase tourist visitors to Indonesia. The video is able to attract foreign youtuber to the range of 173.226 million viewers until mid-March 2017. In effect, the video prompted the Youtubers to do a video reaction, a trend of evaluating video-based expression of videos that are considered phenomenal video. This research is to find visual identity on a video phenomenon that is able to make thousands of youtubers from around the world doing video reaction. Identity is found by the method of analysis between components that are interconnected, so recognize each of its functions that build up the identity of the video. The specified elements are sourced from the results of interviews with the foreign traveler who understand Indonesia and compare it with the representation of Indonesia who lifted the video. Results from the research found some of the main identity among others, the objects raised by the video traveler is a natural that is still original, There are two central figures are filmmakers and indigenous, each place consists of 2 scenes containing activity and activity result, each of which serves as a transition between scenes and perceptions that seem to invite the audience to interact, and the color used is the dominance of monochromatic color is the color that gives the impression of the effect of giving comfort, as well as unify the interaction between humans with nature.